Laser interstitial thermal therapy in the management of bottom‐of‐sulcus dysplasia‐related epilepsy - Bowen Yang; Chao Zhang; Xiu Wang; Baotian Zhao; Jiajie Mo; Weiyuan Luo; Xiaoqiu Shao; Jianguo Zhang; Kai Zhang; Wenhan Hu (Annals of Clinical and Translational Neurology)
Abstract Objective This study assessed the efficacy and safety of magnetic resonance‐guided laser interstitial thermal therapy (MRgLITT) versus open surgery (OS) for the treatment of patients with bottom‐of‐sulcus dysplasia (BOSD)‐related epilepsy. Methods Twenty‐two patients underwent MRgLITT, while 39 underwent OS. Postoperative seizure‐free rates were analyzed using Kaplan–Meier curves. The removal ratio, which represents the extent of damage, was calculated based on preoperative lesion volume and postoperative removal volume. Other outcomes, including adverse events, operative time, and hospital stay, were also compared. Results Kaplan–Meier curves indicated the seizure‐free rates were comparable between the MRgLITT group (90.9%, 26.5 [23.0, 35.1] months) and OS group (89.7%, 25.2 [16.2, 34.6] months) at the final follow‐up (p = 0.901, log‐rank test). The removal ratio of MRgLITT (1.3 [1.1, 1.7]) was significantly lower (p = 0.007) than that of OS (5.8 [3.6, 8.5]). A comparison of postoperative neurological deficits, infection rates, and fever rates revealed no significant differences between MRgLITT and OS groups. The operative time (hours) of MRgLITT (3.0, [2.1, 4.9]) was significantly shorter (p = 0.007) than that of OS (3.5 [3.0, 4.5]). The hospital stay (days) after MRgLITT (6 [5.0, 7.5]) was significantly shorter (p < 0.001) than that of OS (11.0 [9.0, 13.5]). Interpretation MRgLITT has advantages over OS, including comparable seizure control and adverse event profiles, along with reduced removal ratios, shorter operative time, and shorter hospital stays.